Postcolonial turn in Christian theology of religions: some critical aspects - Harmakaputra, Hans Abdiel (Journal of ecumenical studies, 2016)
This essay seeks to analyze the postcolonial method in the contemporary discourse of theology of religions. Kwok Pui-lan and Jenny Daggers will be of importance as the compass of this study, because their works are among the first contributions in postcolonial theology that linked to the field of theology of religions—especially that of Daggers, which is more comprehensive than Kwok’s essay. Kwok delivered a critique toward theology of religions as theological enterprise and proposed a postcolonial theology of difference as the alternative for the former. Daggers, who wrote almost a decade after Kwok, suggested a different direction and attempted a more comprehensive construction of the postcolonial theology of religions. Besides delineating Kwok’s and Daggers’s postcolonial thought, this essay will focus on critical analysis and evaluation of each theologian in order to underline their contributions to the current field of theology of religions. Lastly, it briefly sketches some directions for the construction of the postcolonial theology of religions based on both theologians’ contributions and the author’s experience as an Indonesian Christian.